Implementation of dCas9-mediated CRISPRi in the fission yeast Schizosaccharomyces pombe. Issue 4 (22nd February 2021) - Ishikawa, Ken; Soejima, Saeko; Masuda, Fumie; Saitoh, Shigeaki
Abstract : Catalytically inactive mutant of Cas9 (dCas9) can repress gene transcription. This gene knockdown method, called CRISPRi, is useful because it can repress an arbitrary target gene only by changing the sgRNA sequence that determines target gene specificity. Here, dCas9-mediated CRISPRi is implemented for the deeply studied model organism fission yeast, and a method to design sgRNAs for efficient CRISPRi is offered. This will facilitate revealing gene functions and developing tools based on dCas9 technology in Schizosaccharomyces pombe . Abstract: Controllable and reversible transcriptional repression is an essential method to study gene functions. A systematic knock-down method using catalytically inactive Cas9 (dCas9) was originally established in bacteria. dCas9 forms a ribonucleoprotein with a small guide RNA and uses it to recognize a specific DNA sequence via Watson-Crick base-pairing. When specifically bound to a targeted DNA, dCas9 impairs RNA polymerase activity and represses transcription of that target gene. This technology, CRISPRi, has been implemented in several organisms, but not in Schizosaccharomyces pombe using dCas9. Here, we provide a plasmid that expresses dCas9 and sgRNA in fission yeast. With this plasmid, CRISPRi repressed endogenous gene transcription by as much as 87%. This transcriptional repression method is controllable, reversible, and efficient enough to alter cellular phenotypes. Here, we offer a CRISPRi method to choose proper targeting sequences for transcriptional repression in fission yeast. Implementation of CRISPRi will help to reveal gene functions and to develop tools based on dCas9 technology in S. pombe .